"Physiological Kantianism" and the "organization of the mind": a reconsideration. Issue 4 (2nd October 2021) - Pecere, Paolo
ABSTRACT: In this paper, I reconsider the notion of "physiological Kantianism", applied to Hermann von Helmholtz, Friedrich Lange and other philosophers and scientists of the late nineteenth century. From Hermann Cohen to contemporary scholarship, this designation has been usually referred to a mistaken "naturalization" of Kant's original theory of knowledge in terms of organic structures and dispositions. I argue that, on the contrary, although Helmholtz and Lange indeed endorsed a kind of biological innatism, thus modifying to some extent Kant's original perspective, their views of the physiology of mental processes coexisted with the recognition of the irreducibility of a priori forms and principles to concepts and laws of physiology. I show that this coexistence of transcendental philosophy and physiology was an elaboration that can be traced back to a neglected late essay by Kant himself and hence should be understood as a genuine element of Kant's legacy.